Comparative Investigation of the Spherical Acoustic Microbubble Models in an Unbounded Liquid. - Narmeen N. Nadir; Kawa M.A. MANMI (Zanco Journal of Pure and Applied Sciences, 2020)
Microbubble oscillating associated with many applications in biomedical and engineering sectors. The spherical oscillations of a single microbubble submerged in a quiescent liquid exerted by an acoustic force can be governed either by the Rayleigh-Plesset (RP) equation or by the Keller-Miksis (KM) equation under different physical assumptions. In this paper, both models were numerically and analytically analyzed, and the systematic parametric study was performed. The viscosity and compressibility effects and linearization in both models were investigated with the aids of MATLAB and Maple tools. In KM, the effects of the linear and nonlinear equations of states (EOS) compared for updating density with time. At the minimum bubble radius, the liquid viscosity surrounding bubble surface expected to be decreased due to rising in temperature. This leads to effects the maximum bubble radius for upcoming cycles.